The Historical Impact of the Mongol Invasion on Islamic Civilization: A Study of the Ilkhan Dynasty, Timur Lenk, and Their Socio-Cultural Legacy - Najmudin, Salman; Avicena, Muhamad Zaky; Mulyanudin, Mulyanudin; Hernawan, Wawan; Kusdiana, Ading; Nurcahya, Yan (Jurnal Iman dan Spiritualitas, 2025)
This study aims to analyze the political and social instability experienced by Muslim societies during the Mongol era, particularly during the Ilkhan Dynasty and the reign of Timur Lenk. This study is based on the urgency of understanding the historical roots of disruption in Islamic civilization as a contribution to efforts to prevent future conflict and fragmentation. This study uses historical methods by applying heuristics, source criticism, interpretation, and historiography to reconstruct the events of the Mongol invasion, the establishment of the Ilkhan Dynasty (1260–1343), and the expansion and pacification of Timur Lenk (1370–1404). The research findings show that the Mongol conquests destroyed Islamic political, social, and scientific institutions to a large extent, but simultaneously opened up space for new cultural integration, the Islamization of the Mongol elite, and the formation of a hybrid power structure that combined steppe traditions and Islamic-Persian values. The Ilkhan Dynasty became a space of ideological transition, while Timur Lenk inherited the logic of Mongol military expansion with a strategy of terror and power symbolism. Although both created short-term stability, they failed to build lasting institutional legitimacy. This study contributes to the understanding of the resilience of Islamic civilization, post-conquest power dynamics, and the complex relationship between foreign militarism and the political-religious adaptations of Muslim societies. The research's originality lies in its integrative historical narrative, which links military conquest with its long-term socio-political and cultural impacts on Muslim territories, offering a critical perspective largely unexplored in previous studies.